The Determinants of U.S. Real Interest Rates in the Long Run - Coorey, Sharmini (IMF Working Papers; Working Paper ;, 1991)
This paper examines the factors which influence the behavior of real interest rates in the United States over the long run. Data on real and nominal returns to bonds and equities are tested for unit root non-stationarity. The results indicate that real and nominal interest rates and inflation are integrated of order one while the evidence on returns to equities is mixed. Short- and long-term real rates were found to be cointegrated with government deficits, government debt relative to GNP, private wealth, real balances relative to GNP, demographic factors and the marginal productivity of capital; demographic, fiscal, and monetary policy variables appear to be particularly significant.